Intervention, conception et transformations : Comment construire une prévention durable des TMS ? - Elodie Ciccone; Lucie Cuvelier; Françoise Decortis; Anne Bationo-Tillon (Activités)
The aim of the present paper is to take part in the debate on the role of the ergonomist throughout his/her intervention. It presents an intervention-training on prevention of MSD and painfulness at work. This intervention was conducted as a project. It was based on fundamental principles in activity based ergonomic (Daniellou & Rabardel, 2005). These principals are about (1) design and sustainibility in prevention, (2) effectiveness in ergonomics interventions. Based on our kowlegde and practice background, we postulate that the actors’ involvement in the intervention and the change of their representations/perceptions on their work and health will help increasing the “pouvoir d’agir” (« Power To Act » (Coutarel, Caroly, Vézina, & Daniellou, 2015)) on their safety. Those assumptions are illustrated and discussed using the results of an ergonomic intervention in a duck slaughterhouse.